Strategic Differences in Visual Scanning between Field Dependent and Field Independent individuals on the basis of Eye Tracking Measures - Hamzehzadeh, Marziyeh; Mansouri Sepehr, Rouhollah; Baheshmat, Shahab; Meshki, Vahid; Hashemi Razin, Hadi (International Journal of Applied Behavioral Sciences, 2019)
Introduction: According to previous findings, visual scanning approaches may play a main role in cognitive styles, which is also important in learning processes. This study aimed at comparing field dependent (FD) and field independent (FI) groups in their visual scanning indicators during performance on a set of stimuli. Methods: 68 undergraduate students of Shahid Beheshti University participated in this study through purposive sampling method. Participants were assigned into FD and FI groups through the scores of Group Embedded Figures Test (GEFT). Participants’ eye movements, including fixation details, were tracked by a binocular remote eye-tracking system (SMI-RED120Hz) during their performance on the GEFT. Results: Mixed MANCOVA analyzing was used in this study. Comparing to FD group, FI group fixated their eyes more on the stimuli in shorter time. Revisits were less in FI group and they had longer fixations. Moreover, there were some significant interactive effects among groups and different areas of GEFT. Conclusions: It seems that FI individuals use some practical strategies in their visual scanning which enables them to succeed in differentiating components of a whole picture. These strategies are related to time management and taking new perspectives from which, they can probe the stimuli in more effective methods. Declaration of Interest: None